Protective Role of Hepcidin in Polymicrobial Sepsis and Acute Kidney Injury - Scindia, Yogesh; Wlazlo, Ewa; Leeds, Joseph; Loi, Valentina; Ledesma, Jonathan; Cechova, Sylvia; Ghias, Elizabeth; Swaminathan, Sundararaman (Frontiers in Pharmacology, 2019)
Background: Acute kidney injury (AKI) portends worse prognosis following sepsis, with limited available interventions. Host iron acquisition by pathogens and systemic inflammatory response are key events in the pathogenesis of sepsis. Sepsis induces hepcidin-dependent iron sequestration to limit iron availability to pathogens. Hepcidin also limits inflammation. However, its role in pathophysiology of sepsis-associated AKI is unknown. We investigated role of exogenous hepcidin in endotoxin- and peritonitis-induced pathology and AKI. Methods: C57BL/6 mice were treated with saline or 50-100 μg of hepcidin, pre and post LPS injection or Cecal ligation and puncture (CLP, model of peritonitis). Splenectomized mice (SPLX) were challenged with LPS, with and without Hepcidin. Mice were euthanized at 24 hrs after LPS injection and at different time points after CLP. Systemic inflammation and renal injury markers were assessed. Direct effect of Hepcidin on renal tubular and endothelial cells was evaluated using endotoxin-induced cytotoxic serum. Its effect on LPS stimulated macrophages and role of H-ferritin was evaluated using siRNA to H-ferritin. Results: Twenty-four hrs pretreatment with hepcidin significantly reduced LPS-induced AKI (plasma creatinine, renal NGAL and KIM-1). Hepcidin reduced LPS-induced serum TNF, renal Cox-2, loss in PGC1 and enzymatic activity of cytochrome c oxidase and was associated with reduced glomerular injury and preserved mitochondria. Hepcidin did not directly protect the renal parenchymal cells but reduced endotoxin-induced serum cytotoxicity to mitigate renal injury. SPLX reduced LPS-induced early inflammation and AKI, independent of hepcidin, indicating that regulation of early systemic inflammation may be more important than local events. Higher splenic H-ferritin in hepcidin treated animals was associated with reduced splenocytes apoptosis, and inflammation. Hepcidin treated, H-ferritin-deficient macrophages were less effective in reducing LPS-induced IL-6. Hepcidin significantly reduced CLP-induced AKI, and mortality (20% Hepcidin treated vs 80% PBS treated). Importantly hepcidin reduced bacteremia and AKI even when administered after onset of sepsis. Conclusion: We demonstrate a protective role of hepcidin in endotoxin- and peritonitis-induced pathologies and AKI, exerted through anti-inflammatory effects, and antibacterial property. Macrophage H-ferritin plays an important role in hepcidin-mediated protection against endotoxin-induced inflammation. We uncover a novel prophylactic and therapeutic role of hepcidin in sepsis-associated bacteremia, AKI and mortality.